The situation of the Greek Catholic Church in Slovakia in the second half of 20th century - Peter Šturák (Polonia Sacra)
The past 20th century has many attributes and names. It can be said that it was century of martyrs, but it is also century of the victories of God. In connection with this, ecumenical memory of 20th century martyrs took place on 7th May 2000 in Colosseum in Roma, where Holy Father also said: „At the places, where it seemed that hatred will diminish the whole life and it will be impossible to run from it, witnesses of God showed that love is stronger than death. In terrible systems of tyranny which outraged a man at the places of pain, in hunger and various torments, they showed that they belong to Christ, crucified and resurrected Lord… Let the memory of our brothers and sisters‑martyrs be still alive in following century and millennium. Let it be passed from generation to generation to make deep Christian recovery flow from it. Let guard the memory of martyrs as the jewel of incredible price for the Christians of the new millennium.” These words also fully refer to the Greek Catholic Churuch in Czechoslovakia, which in its history and in the mentioned century underwent hard tests, but it has persevered in faith and loyalty to God. The Greek Catholic Church suffered from pressure of the totalitarian regime the most, it even made its martyrs. While the other Churches were disturbed and weaken, the Greek Catholic Church was directly administratively liquidated.